The impact of mal-angulated femoral rotational osteotomies on mechanical leg axis: a computer simulation model - Jud, Lukas (BMC Musculoskelet Disord, 2020)
BACKGROUND: Subtrochanteric or supracondylar femoral rotational osteotomies are established surgical treatments for femoral rotational deformities. Unintended change of the mechanical leg axis is an identified problem. Different attempts exist to plan a correct osteotomy plane, but implementation of the preoperative planning into the surgical situation can be challenging. Goal of this study was to identify the critical threshold of mal-angulation of the osteotomy plane and of femoral rotation that leads to a relevant deviation of the postoperative mechanical leg axis using a computer simulation approach. METHODS: Three-dimensional (3D) surface models of the lower extremity of two patients (Model 1: 42° femoral antetorsion; Model 2: 6° femoral retrotorsion) were generated from computed tomography data. First, baseline subtrochanteric and supracondylar rotational osteotomies, perpendicular to the femoral mechanical axis were simulated. Afterwards, mal-angulated osteotomies in sagittal and frontal plane followed by different degrees of rotation were simulated and frontal mechanical axis was analyzed. RESULTS: 400 mal-angulated osteotomies have been simulated. Mal-angulation of ±30° with 30° rotation showed maximum deviation from preoperative mechanical axis in subtrochanteric osteotomies (4.0° ± 0.4°) and in supracondylar osteotomies (12.4° ± 0.8°). Minimal mal-angulation of 15° in sagittal plane in subtrochanteric osteotomies and mal-angulation of 10° in sagittal plane in supracondylar osteotomies altered the mechanical axis by > 2°. Mal-angulation in sagittal plane showed higher deviations of the mechanical axis (up to 12.4° ± 0.8°), than in frontal plane mal-angulation (up to 4.0° ± 1.9°). CONCLUSION: A femoral rotational osteotomy, perpendicular to the femoral mechanical axis, has no considerable influence on the mechanical leg axis. However, mal-angulation of femoral rotational osteotomies showed relevant changes of the mechanical leg axis. In supracondylar respectively subtrochanteric procedures, mal-angulation of only 10° in combination with already 15° of femoral rotation respectively mal-angulation of 15° in combination with 30° of femoral rotation, can lead to a relevant postoperative mechanical leg axis deviation of more than 2°, wherefore these patients probably would benefit from the use of navigation aids.